Jogos Sérios para Ensino de Engenharia de Software - Edgar de Sá Alves (2013)
Since the advent of computer games their impact on society is increasing. Increasingly one sees children, teenagers and even adults who spend time playing computer games. This is due to the fact that games have the ability to capture the attention of the player, to stimulate and challenge him, even to be addictive sometimes. Given the importance of computer games in society, arises the idea of creating games that in addition to the entertainment component would include a learning component as well. The aim of this combination is primarily harnessing the ability of games as focal points and entertainment and add them a source of knowledge making them a more enjoyable method of learning. These games, that combine entertainment and learning, are called serious games.This project was developed under a master's thesis, which aims to create a serious game applied to Software Engineering in order to encourage higher education students to study through nicer methods. The developed application is a game that allows one to streamline and encourage the practice of code review, one of the many tasks of Software Engineering. For this project it was important to make an initial study of the state of the art relative to serious games used in Software Engineering to find out what already exists in this area. The definition of the Software Engineering discipline and the areas of knowledge that compose it, were a part of the realized study as well, since it is on them that the problem of this thesis focuses.